Promoting Inclusion and Well-Being Through Inclusive Physical Education and Parasports: an Approach for Adolescents with Motor Impairment - Ben Rakaa, Omar; Bassiri, Mustapha; Lotfi, Said (Physical Education Theory and Methodology, 2025)
Objectives. This study aimed to examine the impact of inclusion students with motor impairment (MI) into adapted physical education (APE) and school para-athletics on their feeling of pedagogical and school inclusion, as well as on their psychological well-being and self-esteem. Materials and Methods. The study involved 96 pupils having motor impairment, aged 16.79 ± 0.87, enrolled in public schools in Morocco. The pupils were divided into three groups according to the para-athletics classification: 30 % (family of 30), 40 % (families of 40) and 30 % (family of 50). The participants were randomly assigned into three groups: a control group with no specific programme, a group following an APE programme (24 sessions), and a third group with APE and additional para-athletics sessions (24 sessions), including competitions for three months. The assessments were carried out before and after the intervention. The scales were employed to gauge self-esteem, psychological well-being, as well as feeling of pedagogical and schooling inclusion. Results. The findings indicate that students who engaged in both the APE and para-athletics programmes exhibited enhancements in their feeling of pedagogical and schooling inclusion, psychological well-being, and self-esteem, when compared to the control group. The group that participated in both APE and para-athletics demonstrated the most significant progress in this study. Conclusions. The findings suggest that the integration of adapted physical education and inclusive sports, including para-athletics, into school curricula in a systematic manner represents a pivotal element in promoting inclusion, well-being and self-esteem among students with motor impairments.